Bio-inspired design: bulk iron–nickel sulfide allows for efficient solvent-dependent CO2 reduction. Issue 4 (14th November 2018) - Piontek, Stefan; junge Puring, Kai; Siegmund, Daniel; Smialkowski, Mathias; Sinev, Ilya; Tetzlaff, David; Roldan Cuenya, Beatriz; Apfel, Ulf-Peter
Abstract : The electrocatalytic reduction of carbon dioxide (CO2 RR) to valuable bulk chemicals is set to become a vital factor in the prevention of environmental pollution and the selective storage of sustainable energy. Abstract : The electrocatalytic reduction of carbon dioxide (CO2 RR) to valuable bulk chemicals is set to become a vital factor in the prevention of environmental pollution and the selective storage of sustainable energy. Inspired by structural analogues to the active site of the enzyme CODHNi, we envisioned that bulk Fe/Ni sulfides would enable the efficient reduction of CO2 . By careful adjustment of the process conditions, we demonstrate that pentlandite (Fe4.5 Ni4.5 S8 ) electrodes, in addition to HER, also support the CO2 RR reaching a peak faradaic efficiency of 87% and 13% for the formation of CO and methane, respectively at 3 mA cm −2 . The choice of solvent, the presence of water/protons and CO2 solubility are identified as key-properties to adjust the balance between HER and CO2 RR in favour of the latter. Such experiments can thus serve as model reactions to elucidate a potential catalyst within gas diffusion electrodes.